Review of Cardiac Anesthesia with 2,100 MCQs (For all Examinations in Cardiac Anesthesia) - Kapoor Poonam Malhotra; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2013)
This book Review of Cardiac Anesthesia with 2,100 MCQs entirely devoted to in-depth coverage of all aspects of cardiac anesthesia with traditional topics on drugs for cardiovascular diseases to congenital heart disease, embryology and rheumatic problems of valves. This is the first book of its kind in cardiac anesthesia and all concerned are masters on the subject. The backbone of any examination today is multiple choice questions. They guide the examinees toward the examination trends. The book is a powerful and most welcome statement about the place of examination trending in the evolving and ever-growing subject of cardiac anesthesia. This book aims at the latter with tables and figures in a simplistic manner for each of the 37 chapters. This book also has MCQs on rapidly developing areas like extracorporeal membrane oxygenation (ECMO), critical care and echocardiography which placed good coverage in this book. Explanations to the MCQs also add value to the book. This book will be fully meet the requirements of students preparing for all examinations in cardiac anesthesia like DM, FNB, FIACTA and perioperative TEE examinations. This book will be very useful to the students especially for those preparing for various competitive examinations. Strongly recommend this student-friendly book to all examinees and examiners of cardiac anesthesia.
Keywords: Anesthesiology,Cardiology,MCQs and Self-assessment; Electronic books